0
$\begingroup$

I would like to prove the equation

$$\frac{\sinh\left(\left (1-\frac{1}{2m} \right)x\right)}{\sinh(x/2m)}=1+ \sum\limits_{n=1}^{m-1}2\cdot \cosh\left(\left( 1-n/m \right)x\right),\quad \forall x > 0, m\in\mathbb{N}.$$

where the sum is evaluated as $0$ for $m=1$.

But I do not see, how to approach this problem. Proof by induction seems not to be appropriate, and it does not seem to be a simple application of the standard addition formulas. Does anyone has an idea?

Best wishes

$\endgroup$
2
$\begingroup$

Substitute $x$ by $mx$. Write $\frac{1}{2}(e^x-e^{-x})$ instead of $\sinh(x)$ and $\frac{1}{2}(e^x+e^{-x})$ instead of $\cosh(x)$. Then you can calculate the right sum by using $\sum\limits_{n=1}^{m-1}z^n=z\frac{z^{m-1}-1}{z-1}$. At the end substitute $x$ by $\frac{x}{m}$.

$\endgroup$
3
$\begingroup$

We have $$\sum_{n=1}^{m-1}2\cosh\left(\left(1-\frac{n}{m}\right)x\right)+1=e^{x}\sum_{n=1}^{m-1}\left(e^{-x/m}\right)^{n}+e^{-x}\sum_{n=1}^{m-1}\left(e^{x/m}\right)^{n}+1 $$ $$=\frac{\left(e^{x}-e^{x/m}\right)\left(1+e^{-x}\right)}{e^{x/m}-1}+1=\color{red}{\frac{\sinh\left(x-\frac{x}{2m}\right)}{\sinh\left(\frac{x}{2m}\right)}}$$ as wanted.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.